2017
DOI: 10.1038/srep45796
|View full text |Cite|
|
Sign up to set email alerts
|

RETRACTED ARTICLE: Chemical inhibition reveals differential requirements of signaling pathways in krasV12- and Myc-induced liver tumors in transgenic zebrafish

Abstract: Previously we have generated inducible liver tumor models by transgenic expression of an oncogene and robust tumorigenesis can be rapidly induced by activation of the oncogene in both juvenile and adult fish. In the present study, we aimed at chemical intervention of tumorigenesis for understanding molecular pathways of tumorigenesis and for potential development of a chemical screening tool for anti-cancer drug discovery. Thus, we evaluated the roles of several major signaling pathways in krasV12- or Myc-indu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
9
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 46 publications
3
9
0
Order By: Relevance
“…In fact, the co-induction of twist1a and xmrk resulted in a 31% increase in the number of apoptotic cells ( Figure 4 A,C). These findings are consistent with those of our previous research on HCC development in other oncogene transgenic zebrafish [ 31 , 35 ]. Remarkably, the percentage of apoptotic cells was higher in transgenic zebrafish with twist1a+ / xmrk+ than in the xmrk+ induction group ( Figure 4 C).…”
Section: Resultssupporting
confidence: 94%
“…In fact, the co-induction of twist1a and xmrk resulted in a 31% increase in the number of apoptotic cells ( Figure 4 A,C). These findings are consistent with those of our previous research on HCC development in other oncogene transgenic zebrafish [ 31 , 35 ]. Remarkably, the percentage of apoptotic cells was higher in transgenic zebrafish with twist1a+ / xmrk+ than in the xmrk+ induction group ( Figure 4 C).…”
Section: Resultssupporting
confidence: 94%
“…3D ). These histological characteristics reproduce the typical morphology and growth patterns of tumors seen in zebrafish 26 . Notice however that although the histo-pathological examination revealed typical tumor morphology, the expression of CFP (and the concomitant oncogene) was no longer detected (Fig.…”
Section: Resultssupporting
confidence: 72%
“…We have previously generated several inducible HCC models in zebrafish by overexpression of an oncogene specifically in hepatocytes [9] , [10] , [11] , [12] , [13] . In our kras V12 -expressing zebrafish HCC model, we have observed a significant liver enlargement in 6-dpf (day post fertilization) larvae after 3 days of induction of kras V12 expression [14] . In the current study, we found that after 4 days of doxycycline exposure, both HSC density and ratio of activation were increased significantly.…”
Section: Introductionmentioning
confidence: 72%